Ritual Boras Si Pir Ni Tondi: Avoiding Problems or Misfortune in Life - Ayu Yunita Sitohang; Suci Rohana Dalimunthe; Sabrina Dwina Azizah; Sesilia Pardosi; Aveni Saulina Nainggolan; Muhammad Ikhwanul Ihsan (Indonesian Journal of Medical Anthropology, 2026)
This study aims to analyze the meaning of the boras si pir ni tondi ritual as a form of protection against danger or misfortune in Batak Toba society. This ritual is a hereditary tradition that continues to be preserved and is believed to possess spiritual power in restoring an individual’s condition after experiencing traumatic events. The research was conducted in two different settings, namely the urban area of Padang Bulan in Medan City and the rural area of Parbuluan Village, Dairi Regency, North Sumatra. A qualitative approach was employed using in-depth interviews with selected informants. The findings indicate that the boras si pir ni tondi ritual has multidimensional meanings, including spiritual aspects as a means of restoring the tondi (soul/spirit), psychological aspects in strengthening mental conditions, and social aspects as a form of adherence to customary norms and reinforcement of kinship solidarity. Furthermore, the ritual embodies symbolic meanings representing affection (holong) and hope for protection from future misfortune. In conclusion, this ritual functions as a holistic recovery mechanism integrating spiritual, psychological, and social dimensions within Batak Toba society.